THE STATUS OF EVIDENCE PROCEEDS OF CRIME IN GENERAL AND MILITARY CRIMES - IRMAN PUTRA; ARIEF FAHMI LUBIS (CV KULTURA DIGITAL MEDIA, 2020)
Determination of the status of evidence of crimes in military courts has the same legal implications as in general courts. Based on the provisions of Article 191 of Law 31 of 1997 concerning Military Courts, it is stated that